An Analysis of Teachers’ Questions in English Language Classroom: A Case Study in Year 10 of SMK N 1 Nunukan - Eka Pratiwi; Yuyun Yulia (Universitas Sarjanawiyata Tamansiswa, 2018)
In English language classroom, teachers’ questions are important parts of teaching English language. Teachers need to know what kind of questions which potentially support students learning target language. However, students did not actively participate in learning particularly when responding teachers’ questions. To overcome this problem, it is important for teachers to modify their question through some techniques in order to get students’ responses. This study reports the types of teachers’ questions used by English teachers in classroom, and the classification of modification questions used by teachers during teaching English language in class.This research belongs to classroom discourse analysis. The research was conducted at tenth grade of SMKN 1 Nunukan. The data were collected through observation, video recording, and interview. The teachers’ questions were analyzed using Miles and Huberman’s (1995) model of qualitative data analysis.The research findings show that both teachers pose more questions of knowledge level than other levels, and the teachers used various techniques to modify their questions when the students did not give response. The modification of modifying questions are repeating and rephrasing. Then sometimes teachers negotiated questions by in Bahasa Indonesia or first language (local language). The domination of knowledge level questions and how teachers modified the questions is influenced by teachers’ competence, students’ competence, situation of teaching English language, and teaching material.